1976
DOI: 10.1002/star.19760280304
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Physicochemical Properties of Rice during Storage

Abstract: The changes in the physicochemical properties of rices which had different amylose contents were studied when the rice was stored at 2°C and 29°C as rough rice, milled rice, defatted milled rice, and as starch. Changes in hardness index, water absorption, stickiness, viscosity, salt‐soluble protein, free fatty acids, and carbonyl compounds during storage are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
57
1
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(66 citation statements)
references
References 21 publications
6
57
1
1
Order By: Relevance
“…According to Juliano the variations occur due to aging process become visible at least 3-4 months after harvesting at 15 0 C [8], [11]. Therefore, this result is in line with the studies done by Juliano.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…According to Juliano the variations occur due to aging process become visible at least 3-4 months after harvesting at 15 0 C [8], [11]. Therefore, this result is in line with the studies done by Juliano.…”
Section: Resultssupporting
confidence: 88%
“…Effects of aging are more prominent in stored non-waxy rice (high amylose) compared to waxy rice [10]. Juliano (1981) stated that minimum three month period is required to observe chemical and physical changes occur due to aging process [11].…”
Section: Introductionmentioning
confidence: 99%
“…Data presented in Table (4) indicated that there was no fixed trend for the effect of storage interval on most of the studied characters except for broken percentage and number of dead and alive insects whereas, means of all other measured traits fluctuated, significantly or insignificantly, with elongation of storage period (Villareal et al, 1976 andDaniels et al, 1998). On the other hand, the three former traits increased with increasing storage duration.…”
Section: Analysis Of Datamentioning
confidence: 96%
“…Local rice milling factories are unwalled and use a traditional ventilation system of natural wind circulation which allows the stored rice to be easily attacked by freely moving insect pests. Moreover, the factories usually keep rice for a few months to a year to reduce the stickiness of rice 12,22 because non-sticky rice is favoured by Thai people. Rice husks and broken residues are left on the floors or in corners of the premises after daily milling operations and no cleaning is usually done.…”
Section: Introductionmentioning
confidence: 99%